PEMANFAATAN APLIKASI TATA NASKAH DINAS ELEKTRONIK (TNDE) DI DINAS KOMUNIKASI, INFORMATIKA DAN STATISTIK KOTA DENPASAR - Pebi Palentini, Ni Kadek; Ginting, Richard Togaranta; Oka Sujana, A.A. Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2021)
This study aims to find out how to use the Aplikasi Tata NaskahDinasElektronik (TNDE) at the DinasKomunikasi, Informatika dan Statistik Kota Denpasar. The author uses a qualitative descriptive analysis method in which the researcher examines a problem thoroughly. The main data in this study are observations, interviews and documentation. These results then indicate that the utilization of the Aplikasi Tata NaskahDinasElektronik (TNDE) has not been optimally carried out by all employees within theDinasKomunikasi, Informatika dan Statistik Kota Denpasar. Utilization of the Aplikasi Tata NaskahDinasElektronik(TNDE) is compiled and based on the PedomanPetunjukPelaksanaan Tata NaskahDinasElektronikArsip Nasional Republik Indonesia which aim is to create good andbased governance e-Government. Keywords: Tata NaskahDinasElektronik, e-Government, DinasKomunikasi, Informatika dan Statistik Kota Denpasar.